Análise espaço-temporal da incidência de leishmaniose tegumentar americana e leishmaniose visceral na cidade de Barreiras/Ba no período de 2010 a 2019 - Dantas, Nadine Luize Barbosa (2021)
Barreiras shows a recent urbanization, accompanied by an intense process of population densification, which causes urban growth with fragile basic health, sanitation and housing infrastructure, interfering with the local population quality of life. Considering that urban growth causes anthropogenic pressure on natural areas and increases the possibilities of transmission of the disease, as the concentration of the human and dog population in cities intensifies, raising the risk of disease outbreaks in urban areas, an attempt was made to understand how deforestation, urban growth and different socioeconomic conditions affect in the incidence of American Tegumentary Leishmaniasis (ATL) and Visceral Leishmaniasis (VL) in the town of Barreiras, in order to clasify the vulnerability to ATL and VL in the period from 2010 to 2019. Therefore, the research engaged to describe the transformations in the spatial distribution of confirmed cases in the town of Barreiras between 2010 and 2019, understand the socio-environmental factors conditioning the proliferation of ATL and VL, observe the incidence of ATL and VL from the transformations in the land use and occupation and qualify, through the method of multivariate analysis, the risk for the occurrence of these diseases. Quali-quantitative research is then executed, an Ecological Study, that used remote sensing data, geoprocessing techniques and digital satellite image processing to perform the spatiotemporal analysis of the distribution patterns of ATL and VL in Barreiras, associating such data to different environmental and socioeconomic conditions. Both leishmaniasis had a higher number of cases between October and April, which is the hottest and wettest period. Visceral leishmaniasis had a higher incidence in urban areas, while tegumentary leishmaniasis predominated in rural areas. The most vulnerable sectors to ATL showed a high rate of suppression of undergrowth, shrubs and trees, high population density and low socioeconomic status. The VL infection occurred in peripheral areas, with a strong indication of poverty, suffering an intense process of urbanization and high suppression of vegetation areas. The results suggest that living and housing patterns influence the population's risk of contamination.